Microscopic mechanisms for the catalyst assisted growth of single-wall carbon nanotubes - Gavillet, J.; Loiseau, A.; Ducastelle, F.; Thair, S.; Bernier, P.; Stephan, O.; Thibault, J.; Thibault, J.
Whatever the synthesis technique used, the growth of ropes of single-wall carbon nanotubes requires the assistance of a metallic catalyst. In this paper, the role played by the catalyst is studied both experimentally and theoretically. Experimentally, the similarities between the samples synthesized from different techniques suggest a common growth mechanism proceeding via the precipitation of excess carbon on metallic nanoparticles. In this paper, the correlation between ropes and catalytic particles is investigated in detail in the case of the Ni-Y catalyst used in the arc discharge technique by combining high resolution transmission electron microscopy, X-ray and electron energy loss spectroscopy. It is shown that the ropes are always found attached to metallic particles about ten times larger than the tube diameter. A further remarkable proof of this relationship is provided by the chemical analyses of the metallic particles. These are found to be free of carbon and to always display the same Ni:Y composition range, whatever the initial Ni:Y composition of the catalyst mixture used in the synthesis, whereas the composition of other particles is highly dispersed. These experimental results support a mechanism of formation based on a vapor-liquid-solid model, in which the tubes of a given bundle nucleate in a cooperative manner and grow at the surface of a same metallic particle. This phenomenological scheme is supported by quantum molecular dynamics simulations which show that carbon atoms are incorporated at the root of a growing tube by a diffusion-segregation process occurring at the surface of the catalytic particle.
Keywords: CARBON NANOTUBES; ARC DISCHARGE; TRANSMISSION ELECTRON MICROSCOPY; MICROSTRUCTURE